A light and high-strength refractory ceramic material and a preparation method thereof

By using lightweight fillers and high refractory materials, combined with fine raw material pretreatment and sintering processes, lightweight high-strength refractory ceramic materials are prepared, which solves the problem of poor performance of existing ceramic materials in high temperature environments, and achieves the lightweight, high strength and good heat resistance of the material.

CN119775031AInactive Publication Date: 2025-04-08JIANGSU ALADING HIGH TEMPERATURE MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411813865.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing refractory ceramic materials do not perform well in high temperature environments, and it is difficult to meet the long-term use requirements in high temperature and high pressure environments. At the same time, the material has a heavier texture and is difficult to adapt to the lightweight needs.

Method used

Lightweight high-strength refractory ceramic materials are prepared through fine raw material pretreatment, mixing and sintering processes using lightweight fillers (such as expanded perlite or glass microbeads), corundum or mullite, silicon carbide and high bauxite.

Benefits of technology

It realizes the lightweight, high strength and good thermal shock resistance of ceramic materials. It is suitable for structural materials or thermal insulation materials in high temperature environments, and has excellent high temperature resistance and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005181241100000101
    Figure BDA0005181241100000101
Patent Text Reader

Abstract

The present invention relates to the technical field of refractory materials, and specifically discloses a lightweight and high-strength refractory ceramic material and a preparation method thereof, comprising 30%-40% lightweight filler (expanded perlite or glass microspheres), 20%-30% corundum or mullite, 10%-15% silicon carbide, 10%-20% high bauxite and 1%-5% dispersant, an oven is used to dry the lightweight filler, a ball mill is used to crush the corundum or mullite and silicon carbide, and a vibrating screen is used to screen them. The present invention ensures that the final ceramic material has the advantages of light weight, high strength, good thermal shock resistance, excellent thermal insulation, high temperature resistance, corrosion resistance, etc., is suitable for structural materials or thermal insulation materials in high temperature environments, and the precise control of humidity, temperature and molding pressure during the preparation process improves the uniformity and performance stability of the material, ensuring an efficient production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a lightweight and high-strength refractory ceramic material and a preparation method thereof. Background Art

[0002] Refractory materials refer to materials that can maintain their shape and performance in high-temperature environments. They are usually used in high-temperature furnaces, heat treatment equipment, rocket engines and other places that need to withstand extremely high temperatures. Refractory materials are mainly composed of high-temperature resistant minerals and have high heat resistance, chemical stability and mechanical strength. Ceramics refer to inorganic non-metallic materials made from natural minerals (such as clay, feldspar, quartz, etc.) fired at high temperatures. They have the characteristics of hardness, wear resistance, heat resistance, and corrosion resistance. Refractory materials are a special type of ceramics that focus on high-temperature applications such as high temperature resistance and thermal shock resistance.

[0003] However, existing refractory ceramics generally lack strength and stability, and have poor performance in high-temperature long-term stability and other aspects, making it difficult to meet the long-term use requirements in harsh environments such as high temperature and high pressure. In addition, general ceramic materials are heavy in texture and difficult to adapt to lightweight usage scenarios, and lightweight ceramics will inevitably lead to reduced material strength. Therefore, the present invention proposes a lightweight and high-strength refractory ceramic material and a preparation method thereof to solve the problems mentioned in the above background technology. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a lightweight and high-strength refractory ceramic material and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a lightweight and high-strength refractory ceramic material, comprising the following components by mass percentage:

[0007] 30%-40% lightweight filler (expanded perlite or glass microspheres), 20%-30% corundum or mullite, 10%-15% silicon carbide, 10%-20% high bauxite and 1%-5% dispersant.

[0008] The preparation method specifically comprises the following steps:

[0009] S1. Raw material pretreatment: Use an oven to dry the lightweight filler at a temperature of 80-120°C for 2-4 hours until the moisture content of the filler is less than 0.5% to avoid cracks caused by water vapor during molding;

[0010] The corundum or mullite and silicon carbide are crushed by ball mill and screened by vibrating screen. The diameter of crushed corundum or mullite particles is controlled below 80 meshes, and the diameter of silicon carbide particles is controlled below 100 meshes to ensure particle refinement and provide better mixing effect and surface contact.

[0011] Prepare a regulator, which is polyvinyl alcohol (PVA). Dissolve the regulator polyvinyl alcohol (PVA) particles in water at a concentration of 2%-5%. Polyvinyl alcohol is soluble in water to form a viscous solution, which can effectively improve the wettability of ceramic powder during the mixing process and improve the fluidity and formability of the raw materials.

[0012] S2. Raw material mixing: the pretreated raw materials are mixed by wet mixing. All raw materials are accurately weighed according to the designed ratio by a planetary mixer and then mixed. A certain amount of water in which the polyvinyl alcohol is dissolved is added during the mixing process. The amount of water added accounts for 10%-15% of the total mass of the raw materials. The final mixture does not adhere to the equipment, the particles are uniform, and there is no obvious lumps or agglomerates to ensure that the mixture can reach a suitable humidity (the common humidity is 15%-20%).

[0013] S3, raw material molding, using dry pressing mold pressing, the clay material in step S2 is pressed into a desired shape, and the final mixture in S2 is pressed and molded by a hydraulic molding machine. The molding pressure is set at 15-30MPa, and the pressure is adjusted according to the adhesion of the raw materials. The mold design needs to ensure uniform shape to avoid pores or cracks.

[0014] S4, drying and sintering, drying the formed ceramic body, using a tunnel furnace to dry the ceramic body in step S3, the drying temperature is set at 100-120°C, the duration is 8-12h, until the moisture content of the body drops below 0.5%, remove excess moisture, and avoid cracks during the sintering process;

[0015] The dried green body is sintered in a heat-proof high-temperature kiln. During the sintering process, the lightweight filler will expand to form a microporous structure, reducing the material density. The high-temperature kiln is set to a temperature in the range of 1500-1700℃ for sintering. The sintering time is usually 6-10h, and the heating rate is set to 2-5℃ / min to avoid stress concentration and cracks caused by rapid heating. After sintering, the cooling rate is 2-5℃ / min to avoid thermal shock problems. The density of the sintered ceramic should be controlled at 2.0-2.4g / cm 3 within the range.

[0016] A light and high-strength refractory ceramic material is prepared according to the preparation method.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The advantages of the preparation method of the present invention lie in the fine raw material pretreatment and mixing process. The lightweight filler is dried in an oven and its moisture content is controlled to avoid cracks caused by water vapor during molding. For materials such as corundum, mullite and silicon carbide, ball milling and vibrating screen are used to ensure particle refinement, making the mixing more uniform and improving the surface contact of the materials. Polyvinyl alcohol (PVA) is used as a regulator for wet mixing to improve the fluidity and wettability of the raw materials, avoid agglomeration of the mixture, and further improve the stability of molding and pressing;

[0019] 2. In the forming process of the present invention, dry pressing is performed by a hydraulic forming machine at an appropriate pressure (15-30MPa) to ensure the uniformity of the ceramic body and reduce the generation of pores or cracks. The temperature and time control of the sintering process are very strict. The setting of the heating rate and the cooling rate effectively avoids cracks caused by thermal stress and ensures the density and strength of the ceramic material after sintering. In particular, the expansion effect of the lightweight filler makes the final ceramic material have a microporous structure, thereby reducing the material density and improving the thermal insulation performance;

[0020] 3. The ceramic material prepared by the present invention has the advantages of light weight and high strength. By using lightweight fillers such as expanded perlite or glass beads, the density of the ceramic material is controlled at 2.0-2.4g / cm 3 While maintaining a high compressive strength, the microporous structure effectively disperses the stress and enhances the thermal shock stability of the material. High refractory materials such as corundum and mullite ensure the long-term stability of the ceramic at extremely high temperatures and adapt to the use requirements of high temperature environments. Good corrosion resistance and acid and alkali resistance enable this ceramic material to maintain excellent performance in harsh environments.

[0021] In summary, the preparation method of the present invention ensures that the final ceramic material has the advantages of light weight, high strength, good thermal shock resistance, excellent thermal insulation, high temperature resistance, corrosion resistance, etc. through reasonable raw material selection, pretreatment, mixing, molding and sintering processes. It is suitable for structural materials or thermal insulation materials in high temperature environments. In addition, the precise control of humidity, temperature and molding pressure during the preparation process improves the uniformity and performance stability of the material, ensuring an efficient production process. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0023] Example 1

[0024] A method for preparing a lightweight and high-strength refractory ceramic material, comprising the following components by mass percentage:

[0025] 40% lightweight filler glass beads, 30% mullite, 15% silicon carbide, 10% high bauxite and 5% dispersant.

[0026] The preparation method specifically comprises the following steps:

[0027] S1. Raw material pretreatment: Use an oven to dry the lightweight filler at a temperature of 90°C for 2 hours until the moisture content of the filler is less than 0.5% to avoid cracks caused by water vapor during molding;

[0028] Furthermore, a ball mill is used to crush the corundum or mullite and silicon carbide, and a vibrating screen is used to screen the corundum or mullite particles, wherein the diameter of the crushed particles is controlled to be below 80 meshes, and the diameter of the silicon carbide particles is controlled to be below 100 meshes, so as to ensure particle refinement and provide better mixing effect and surface contact;

[0029] Furthermore, a regulator is prepared, and the regulator is polyvinyl alcohol (PVA). The regulator polyvinyl alcohol (PVA) particles are dissolved in water at a concentration of 3%. Polyvinyl alcohol is soluble in water to form a viscous solution, which can effectively improve the wettability of the ceramic powder during the mixing process and improve the fluidity and formability of the raw materials.

[0030] S2. Raw material mixing: the pretreated raw materials are mixed by wet mixing. All raw materials are accurately weighed according to the designed ratio by a planetary mixer and then mixed. A certain amount of water in which the polyvinyl alcohol is dissolved is added during the mixing process. The amount of water added accounts for 10%-15% of the total mass of the raw materials. The final mixture does not adhere to the equipment, the particles are uniform, and there is no obvious lumps or agglomerates to ensure that the mixture can reach a suitable humidity (the common humidity is 15%-20%).

[0031] S3, raw material molding, using a dry pressing mold to press the clay material in step S2 into a desired shape, and using a hydraulic molding machine to press the final mixture in S2. The molding pressure is set at 15 MPa, and the pressure is adjusted according to the adhesion of the raw materials. The mold design needs to ensure uniform shape to avoid pores or cracks.

[0032] S4, drying and sintering, drying the formed ceramic body, using a tunnel furnace to dry the ceramic body in step S3, the drying temperature is set at 100°C, the duration is 8 hours, until the moisture content of the body drops below 0.5%, remove excess moisture, and avoid cracks during the sintering process;

[0033] Furthermore, the dried green body is sintered in a heat-proof high-temperature kiln. During the sintering process, the lightweight filler will expand to form a microporous structure, reducing the material density. The high-temperature kiln is set to a temperature in the range of 1650°C for sintering. The sintering time is usually 8 hours, and the heating rate is set to 2°C / min to avoid stress concentration and cracks caused by rapid heating. After sintering, the cooling rate is 5°C / min to avoid thermal shock problems. The density of the sintered ceramic should be controlled at 2.0-2.4g / cm 3 within the range.

[0034] Example 2

[0035] A method for preparing a lightweight and high-strength refractory ceramic material, comprising the following components by mass percentage:

[0036] 35% lightweight filler glass beads, 25% corundum, 15% silicon carbide, 20% high bauxite and 5% dispersant.

[0037] The preparation method specifically comprises the following steps:

[0038] S1. Raw material pretreatment: Use an oven to dry the lightweight filler at a temperature of 100°C for 4 hours until the moisture content of the filler is less than 0.5% to avoid cracks caused by water vapor during molding;

[0039] Furthermore, a ball mill is used to crush the corundum or mullite and silicon carbide, and a vibrating screen is used to screen the corundum or mullite particles, wherein the diameter of the crushed particles is controlled to be below 80 meshes, and the diameter of the silicon carbide particles is controlled to be below 100 meshes, so as to ensure particle refinement and provide better mixing effect and surface contact;

[0040] Furthermore, a regulator is prepared, and the regulator is polyvinyl alcohol (PVA). The regulator polyvinyl alcohol (PVA) particles are dissolved in water at a concentration of 5%. Polyvinyl alcohol is soluble in water to form a viscous solution, which can effectively improve the wettability of the ceramic powder during the mixing process and improve the fluidity and formability of the raw materials.

[0041] S2. Raw material mixing: the pretreated raw materials are mixed by wet mixing. All raw materials are accurately weighed according to the designed ratio by a planetary mixer and then mixed. A certain amount of water in which the polyvinyl alcohol is dissolved is added during the mixing process. The amount of water added accounts for 10%-15% of the total mass of the raw materials. The final mixture does not adhere to the equipment, the particles are uniform, and there is no obvious lumps or agglomerates to ensure that the mixture can reach a suitable humidity (the common humidity is 15%-20%).

[0042] S3, raw material molding, using a dry pressing mold to press the clay material in step S2 into a desired shape, and using a hydraulic molding machine to press the final mixture in S2. The molding pressure is set at 30 MPa, and the pressure is adjusted according to the adhesion of the raw materials. The mold design needs to ensure uniform shape to avoid pores or cracks.

[0043] S4, drying and sintering, drying the formed ceramic body, using a tunnel furnace to dry the ceramic body in step S3, the drying temperature is set at 120° C., the duration is 10 hours, until the moisture content of the body drops below 0.5%, remove excess moisture, and avoid cracks during the sintering process;

[0044] Furthermore, the dried green body is sintered in a heat-resistant high-temperature kiln. During the sintering process, the lightweight filler will expand to form a microporous structure, reducing the material density. The high-temperature kiln is set to a temperature within the range of 1700°C for sintering. The sintering time is usually 9 hours, and the heating rate is set to 2°C / min to avoid stress concentration and cracks caused by rapid heating. After sintering, the cooling rate is 5°C / min to avoid thermal shock problems. The density of the sintered ceramic should be controlled at 2.0-2.4g / cm 3 within the range.

[0045] Example 3

[0046] A method for preparing a lightweight and high-strength refractory ceramic material, comprising the following components by mass percentage:

[0047] 30% lightweight filler expanded perlite, 30% mullite, 15% silicon carbide, 20% high bauxite and 5% dispersant.

[0048] The preparation method specifically comprises the following steps:

[0049] S1. Raw material pretreatment: Use an oven to dry the lightweight filler at a temperature of 105°C for 3 hours until the moisture content of the filler is less than 0.5% to avoid cracks caused by water vapor during molding;

[0050] Furthermore, a ball mill is used to crush the corundum or mullite and silicon carbide, and a vibrating screen is used to screen the corundum or mullite particles, wherein the diameter of the crushed particles is controlled to be below 80 meshes, and the diameter of the silicon carbide particles is controlled to be below 100 meshes, so as to ensure particle refinement and provide better mixing effect and surface contact;

[0051] Furthermore, a regulator is prepared, and the regulator is polyvinyl alcohol (PVA). The regulator polyvinyl alcohol (PVA) particles are dissolved in water at a concentration of 5%. Polyvinyl alcohol is soluble in water to form a viscous solution, which can effectively improve the wettability of the ceramic powder during the mixing process and improve the fluidity and formability of the raw materials.

[0052] S2. Raw material mixing: the pretreated raw materials are mixed by wet mixing. All raw materials are accurately weighed according to the designed ratio by a planetary mixer and then mixed. A certain amount of water in which the polyvinyl alcohol is dissolved is added during the mixing process. The amount of water added accounts for 10% of the total mass of the raw materials. The final mixture does not adhere to the equipment, the particles are uniform, and there is no obvious lumps or agglomerates to ensure that the mixture can reach a suitable humidity (the common humidity is 15%-20%).

[0053] S3, raw material molding, using a dry pressing mold to press the clay material in step S2 into a desired shape, and using a hydraulic molding machine to press the final mixture in S2. The molding pressure is set at 25 MPa, and the pressure is adjusted according to the adhesion of the raw materials. The mold design needs to ensure uniform shape to avoid pores or cracks.

[0054] S4, drying and sintering, drying the formed ceramic body, using a tunnel furnace to dry the ceramic body in step S3, the drying temperature is set at 110° C., the duration is 9 hours, until the moisture content of the body drops below 0.5%, remove excess moisture, and avoid cracks during the sintering process;

[0055] Furthermore, the dried green body is sintered in a heat-proof high-temperature kiln. During the sintering process, the lightweight filler will expand to form a microporous structure, reducing the material density. The high-temperature kiln is set to a temperature in the range of 1550°C for sintering. The sintering time is usually 10 hours, and the heating rate is set to 5°C / min to avoid stress concentration and cracks caused by rapid heating. After sintering, the cooling rate is 5°C / min to avoid thermal shock problems. The density of the sintered ceramic should be controlled at 2.0-2.4g / cm 3 within the range.

[0056] Comparative Example 1

[0057] The preparation method of the lightweight high-strength refractory ceramic material provided in this comparative example is the same as that of Example 1, except that no lightweight filler is added.

[0058] Comparative Example 2

[0059] The preparation method of the lightweight and high-strength refractory ceramic material provided in this comparative example is the same as that of Example 1, except that no corundum or mullite is added.

[0060] Comparative Example 3

[0061] The preparation method of the lightweight and high-strength refractory ceramic material provided in this comparative example is the same as that of Example 1, except that silicon carbide is not added.

[0062] Performance of various embodiments and comparative examples

[0063]

[0064] Porosity refers to the volume ratio of pores in ceramics, usually expressed as a percentage. Ceramics with low porosity usually have better mechanical properties and anti-permeability properties. The porosity is usually between 20% and 40%. For high-strength and high-density ceramics, the porosity should be controlled within 5% to 10%. In the above embodiment, due to the addition of lightweight fillers and the expanded microporous structure, the porosity of the ceramic material obtained by the preparation method is maintained at about 30%, which is higher than that of general high-density ceramics.

[0065] Compressive strength refers to the maximum compressive stress that ceramics can withstand when subjected to axial pressure. The compressive strength of high-quality ceramics should reach 50-100 MPa or more. The strength of the above-mentioned embodiments is above 100, which has excellent compressive performance. However, the strength of the comparative examples is at an average level.

[0066] Refractory performance refers to the ability of ceramics to maintain stable shape and mechanical properties in a high temperature environment, and is usually measured by refractoriness. The refractoriness of common ceramic materials should generally reach 1600°C-1800°C or above, and the refractoriness of the above-mentioned embodiments reaches about 2200°C, which is higher than that of the comparative examples. The ceramic materials of the embodiments can withstand thermal stress for a long time at high temperatures without deformation or melting.

[0067] Thermal shock stability refers to the ability of ceramics to resist cracking or breaking when experiencing rapid temperature changes. Thermal shock stability can be evaluated by thermal shock cycle testing. Good thermal shock stability is usually manifested as no cracks or breaks in the ceramics after 100-200 cycles of temperature changes. The thermal shock stability of the above-mentioned embodiments all reaches more than 300 times, which is significantly higher than that of the comparative examples, indicating that the ceramic materials of the embodiments can maintain structural integrity in a high-temperature and rapidly changing environment;

[0068] Water absorption rate refers to the proportion of water that ceramics can absorb under standard conditions. For ceramics with high water resistance requirements, the water absorption rate should be less than 1%. The water absorption rates of the above-mentioned embodiments are all maintained below 0.1%, which is significantly improved compared with the comparative examples. This means that the ceramic material prepared in the embodiments is not easily affected by moisture and has better durability and stability.

[0069] In summary, the ceramic material prepared in this embodiment still maintains high compressive strength and thermal shock stability despite the significant increase in porosity. At the same time, the high porosity brings a lighter usage experience compared to traditional ceramic materials. The embodiment also performs outstandingly in terms of refractoriness and water absorption, indicating that the ceramic material is suitable for applications in high temperature, high pressure and harsh environments, and has good durability and stability, and is suitable for use in high-strength, high-temperature resistant and water-resistant engineering scenarios.

[0070] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a lightweight and high-strength refractory ceramic material, characterized in that: Calculated by mass percentage, it includes the following components: 30%-40% lightweight filler (expanded perlite or glass microspheres), 20%-30% corundum or mullite, 10%-15% silicon carbide, 10%-20% high bauxite and 1%-5% dispersant. The preparation method specifically comprises the following steps: S1. Pre-treatment of raw materials: drying lightweight fillers, crushing and screening corundum, mullite and silicon carbide to ensure uniform particles and suitable for subsequent mixing, preparing regulators and ensuring the formability of materials; S2, raw material mixing, the pre-treated raw materials are mixed by wet mixing, and a certain amount of water is added during the mixing process to achieve a suitable molding humidity; S3, forming the raw materials, using a dry pressing mold to press the clay material in step S2 into a desired shape; S4, drying and sintering, drying the formed ceramic body to remove excess moisture and avoid cracks during the sintering process. The dried body is sintered in a heat-proof high-temperature kiln. During the sintering process, the lightweight filler will expand to form a microporous structure and reduce the material density.

2. The method for preparing a lightweight and high-strength refractory ceramic material according to claim 1, characterized in that: In step S1, the lightweight filler is dried in an oven at a temperature of 80-120° C. for 2-4 hours until the moisture content of the filler is less than 0.5% to avoid cracks caused by water vapor generated during molding.

3. The method for preparing a lightweight and high-strength refractory ceramic material according to claim 1, characterized in that: In the step S1, a ball mill is used to crush the corundum or mullite and silicon carbide, and a vibrating screen is used to screen them, wherein the diameter of the crushed particles of corundum or mullite is controlled to be below 80 meshes, and the diameter of the silicon carbide particles is controlled to be below 100 meshes, so as to ensure particle refinement and provide better mixing effect and surface contact.

4. The method for preparing a lightweight and high-strength refractory ceramic material according to claim 1, characterized in that: In the step S1, the regulator is polyvinyl alcohol (PVA). The regulator polyvinyl alcohol (PVA) particles are dissolved in water at a concentration of 2%-5%, and mixed into the raw materials in the step 2. Polyvinyl alcohol is soluble in water to form a viscous solution, which can effectively improve the wettability of the ceramic powder during the mixing process and improve the fluidity and formability of the raw materials.

5. The method for preparing a lightweight and high-strength refractory ceramic material according to claim 1, characterized in that: In step S2, all raw materials are accurately weighed and mixed according to the designed proportion using a planetary mixer, and the amount of water added accounts for 10%-15% of the total mass of the raw materials. The final mixture does not adhere to the equipment, the particles are uniform, and there is no obvious clump or agglomeration, so as to ensure that the mixture can reach a suitable humidity (common humidity is 15%-20%).

6. The method for preparing a lightweight and high-strength refractory ceramic material according to claim 1, characterized in that: In step S3, a hydraulic molding machine is used to press-form the final mixture in S2. The molding pressure is set at 15-30 MPa. The pressure is adjusted according to the adhesion of the raw materials. The mold design needs to ensure uniform shape to avoid pores or cracks.

7. The method for preparing a lightweight and high-strength refractory ceramic material according to claim 1, characterized in that: In step S4, a tunnel furnace is used to dry the ceramic body in step S3, the drying temperature is set at 100-120° C., and the duration is 8-12 hours, until the moisture content of the body drops below 0.5%; Use a high temperature kiln and set the temperature in the range of 1500-1700℃ for sintering. The sintering time is usually 6-10h, and the heating rate is set to 2-5℃ / min to avoid stress concentration and cracks caused by rapid heating. After sintering, the cooling rate is 2-5℃ / min to avoid thermal shock problems. The density of the ceramic after sintering should be controlled at 2.0-2.4g / cm 3 within the range.

8. A lightweight and high-strength refractory ceramic material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

Citation Information

Cited By

  • Functional ceramic blank and preparation method thereof

    CN120398569A

  • A functional ceramic green body and a method for preparing the same

    CN120398569B